A Laboratory Method for Determining Bacterially Formed Odorants and Reducing Odor in Absorbent Incontinence Products. Issue 6 (November 2019) - Ryttsén, Frida; Lafqvist, Sofia; Wall, Torun; Forsgren-Brusk, Ulla; Larsson, Peter
Abstract : PURPOSE: The purpose of this study was to design a laboratory test method to mimic the formation of bacterially formed odorants during the use of absorbent urinary incontinence products. Three odor inhibitors with different modes of action were tested and evaluated. METHODS: Bacterially formed odorants in incontinence products were evaluated by adding a synthetic urine inoculated with a mixture of 4 bacterial strains to product samples cut from the incontinence products. The product samples were incubated in sealed flasks. The odorants that formed in the head space were sampled onto adsorbent tubes and analyzed by gas chromatography. The inhibitory effects of low pH, ethylenediaminetetraacetic acid (EDTA), and activated carbon were then measured. RESULTS: This technique enabled production of known odorants 3-methylbutanal, guaiacol, diacetyl, and dimethyl disulfide (DMDS) in concentrations of 50 to 600 ng/L in incontinence products. The method was further evaluated by testing 3 types of odor inhibitors; EDTA significantly reduced formation of all 4 odorants ( P < .001). Lowering the pH from 6.0 to 4.9 decreased levels of 3-methylbutanal, DMDS, and guaiacol ( P < .001); however, diacetyl levels increased ( P < .001). Activated carbon significantly reduced the formation of diacetyl, DMDS, guaiacol, and 3-methylbutanal ( P < .001). CONCLUSIONS: The technique we developed can be used to evaluate inhibitors with different modes of action to determine odor control in incontinence products. The odorants formed are produced by bacteria and have been identified as key contributors to the odor of used incontinence products. This work can be a step toward establishing a standard in the field of incontinence and odor control; creation of a standard will help the health care sector compare products to be purchased and benefit patients through the development of better products.